A need towards Mass Customerizing Kerala Tourism - Sindhu R Babu and Suresh Subramoniam
Development of a country or a region is attributed to the successful growth of industries or sectors involved. Tourism is one such industry which is considered as the largest foreign exchange earner and is growing at a very fast pace especially in developing countries. There is a sea change in the tourist behaviour as well when compared to the traditional tourist with regard to planning, booking/cancellation or payment. The simplicity, easiness, faster response rate, lesser transaction cost, competitive prices and Internet based shopping can be some of the features of the e business which attracts the tourist from the world over. Hence the paper tries to enumerate the IT initiatives taken up by Kerala state tourism department. Also it gives an insight on the upcoming project and the budget allocated. It also gives suggestions regarding improving tourism by adopting the concept of Mass Customerization to woo more number of tourists